Web Store Teh Krisan (erpekrisan) Rachmat Purnama Farm - Medhanita Dewi Renanti; Anita Ristianingrum; Leni Lidya (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
The Rachmat Purnama Farm Company, a producer of chrysanthemum flowers located in Cianjur Regency, has made efforts to process chrysanthemum flowers into chrysanthemum tea. However, the marketing remains limited, as sales are conducted directly. Consequently, the company recognizes the need for an online web store to enhance its marketing reach. The purpose of this system is to provide customers with information about chrysanthemum tea and facilitate convenient purchase transactions. The waterfall model is used as the software development method, which covers requirements analysis, system design, program code development, program testing, and program implementation and maintenance. The features of the online web store include account management, customer management, product categorization, product listings, attributes, sales, payments, shipping, and transaction reports. The implementation has positively impacted the company’s sales of chrysanthemum tea products, as shown by the increasing number of online purchases. Moreover, the marketing area coverage has expanded to Jakarta and Kalimantan.